Surviving antibiotic treatment as a gut bacterium: genomic characterization of an Enterobacter cloacae - Anna Baborski; Stefanie A. Barth; Elke Martina Jung; Frank Bloos; Jürgen Rödel; Bettina Löffler; Michael Bauer; Anne Busch (BMC Genomic Data)
Abstract Enterobacter cloacae complex is a group of common opportunistic pathogens on intensive care units. On intensive care units sepsis is treated with high doses of antibiotics. This treatment does not only eliminate pathogenic bacteria but parts of the microbiome community as well. This leads to an imbalance of the gut microbiome. However, some bacteria can survive such treatment due to certain survival and resistance mechanisms. Not only antibiotic resistance mechanisms but also forming strong communities via biofilm formation promotes cell survival. Here, we investigated the properties of the isolate AT70PIP076 from a sepsis patient treated with piperacillin and tazobactam. After biochemical analysis and MALDI-TOF analysis, the strain was found to be Enterobacter cloacae. In addition to in vitro, antimicrobial susceptibility testing the genome was further investigated in situ regarding antibiotic resistance. Further live/dead staining was performed, and the biofilm formation was investigated using confocal laser microscopy (cLSM). The genome shows the presence of biofilm-associated genes EU554560, bcsABZC_AP010953, ehaB, KF662843, and crl. The understanding of the underlying mechanism of survival of potential pathogens might contribute to elucidate potential treatment options. ObjectivesGenomic analysis of a bacterium that can survive antibiotic treatment within the gut of an antibiotictreated patient to elucidate survival and resistance mechanisms. Data descriptionThe isolate AT70PIP076 was isolated in 2021 from feces collected from a patient treated with Piperacillin and tazobactam. Whole genome DNA was isolated using the Nextera DNA Flex microbial colony extraction protocol and the Nextera Flex DNA preparation kit according to the manufacturer’s instructions. Following paired-end sequencing was performed on the MiSeq platform (Illumina, Inc., San Diego, CA, USA) using a 300-cycle MiSeq reagent kit and a read length of 151 bp. Contamination check and identification of 16 S RNA sequences was done by using ContESt16S. The genomic sequence contained 4,988,237 bp and the G + C content is represented at 54.80%. This genome and its associated data set will serve as a useful resource for further analyses.